OPTIMALISASI SISTEM INFORMASI DALAM MENINGKATKAN PELAYANAN PUBLIK DI DUSUN TEMANGGUNG, JETIS, SAPTOSARI, GUNUNGKIDUL - S Sakir; Azam Syukur Rahmatullah; Riska Sarofah (WARTA LPM, 2019)
Social empowerment activities are carried out with two main activities, namely the making of profile village and Strengthening of Village Information System (SID) at Temanggung Cluster, Jetis Saptosari, Gunung Kidul Regency. Potentials possessed by the hamlet should be able to be the identity of the development of village progress. The method used is to assist and involve students of Universitas Muhammadiyah Yogyakarta to directly go to the field and develop/arrange the profile of hamlet and website creation and training to realize the reliable human resources. Outputs resulting from community service include; first, Temanggung has a profile book with the latest edition and with the addition of necessary information. Second, Temanggung has a website that contains information of hamlet and village. The proposed developments after the program are updating village profiles and utilizing social media in the provision of services other than websites that have been created by empowerment community. Keywords: Village, Profile, Information, System